Effect of Contamination on Electric Field Distribution of DC Voltage Divider - Caibo Liao; Ruan Jiangjun; Du Zhiye; Liu Chao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to research the influence of the contamination around the external insulating surface of DC voltage divider with different types in the electic field distribution by using the finite element method, a two dimensional axisymmetric model of the DC voltage divider in Longquan convertor station is built. Through the calculation comparison in electrostatic and quasi-electrostatic field, the relative dielectric constant of the dry, moist and the non-uniform mixed contamination layer is discussed under the condition of the material parameters is known in quasi-electrostatic field .Analysis shows that for dry contamination，the field type has no influence on the electric field distribution when the parameters of the materials are same. While for moist contamination，the relative dielectric constant in electrostatic field should be set according to the material resistivity in quasi-electrostatic field and the actual condition. The calculation of the non-uniform contamination prove that the materials parameters in electrostatic filed is reasonable.